Partitioning of Bronchopulmonary Carcinoids in Two Different Prognostic Categories by Ki-67 Score - Grimaldi, Franco; Muser, Daniele; Beltrami, Carlo Alberto; Machin, Piernicola; Morelli, Angelo; Pizzolitto, Stefano; Talmasson, Giovanni; Marciello, Francesca; Colao, Annamaria A.; Monaco, Roberto; Monaco, Guglielmo; Faggiano, Antongiulio (Frontiers in Endocrinology, 2011)
Introduction: Histological distinction between typical and atypical bronchopulmonary carcinoids is based on mitotic activity and necrosis. Regardless of these two parameters, outcome after surgery is often unpredictable. In this study the prognostic value of different clinico-pathological factors was retrospectively analyzed in a large series of patients with bronchopulmonary carcinoid. Patients & Methods: The long-term postsurgical outcome of 106 radically treated patients affected by bronchopulmonary carcinoid from 2 Italian centers was correlated with tumor characteristics assessed by combining conventional histology with a panel of immunohistochemical markers of neuroendocrine differentiation (chromogranin-A, NSE) and proliferation activity (Ki-67 score). Results: Carcinoids were assessed as typical (TC=75; 70.8%) and atypical (AC=31; 29.2%). Mean follow-up was 8.3 years (range: 0-20; median: 8.0). All cases expressed neuroendocrine markers. At univariate analysis, tumor recurrence [14/75 TC (18.7%), 15/31 AC (48.4%)] correlated with carcinoid histotype (P = 0.003), tumor size (P = 0.012), mitotic index (P = 0.044), Ki-67 score (P < 0.0001), and synchronous node metastasis (P = 0.037). Of these, Cox multivariate analysis confirmed only Ki-67 score as independent predictor of disease recurrence (P = 0.009). The best cut-off for Ki-67 score (calculated by ROC curves) discriminating recurrent versus non recurrent disease was 4% (sensitivity 79.3%; specificity 83.8%; area under the curve 0.85). By stratifying patients according to this cut-off, a significantly different disease-free survival was found (log-rank test P < 0.0001). Conclusions: Ki-67 score accurately separates bronchopulmonary carcinoids in two well-distinct histo-prognostic categories. Ki-67 score predicts the patient’s outcome better than mitotic count, histotype and tumor stage and it is therefore helpful in establishing the appropriate follow-up.